Doping in sports: Knowledge and attitudes among parents of Austrian junior athletes - Blank, C.; Leichtfried, V.; Schaiter, R.; Fürhapter, C.; Müller, D.; Schobersberger, W. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Strategies for doping prevention are based on prior identification of opportunities for intervention. There is no current research focusing on the potential role in doping prevention, which might be played by the parents of junior elite athletes. The purpose of this study was to evaluate the knowledge and attitudes toward doping among parents of Austrian junior athletes and to analyze factors potentially influencing these beliefs. In this study, two questionnaires were distributed to 1818 student athletes, each with instructions that these surveys were to be completed by their parents (ntotal = 3636). Parents filled in questionnaires at home without observation. Responses from 883 parents were included in this analysis. Compared to female parents, male parents demonstrated significantly better knowledge about doping and its side effects and were more likely to be influenced by their own sporting careers and amounts of sports activities per week. Parental sex did not demonstrate a significant influence on responses reflecting attitudes toward doping. Additional research is needed to compare these results with young athletes' knowledge and attitudes to determine if and to what degree parental attitudes and beliefs influence the behavior and attitudes of their children.